Bibliometric Analysis of Ebola Research Indexed in Web of Science and Scopus (2010-2020). (3rd September 2020) - Kawuki, Joseph; Yu, Xiaojin; Musa, Taha Hussein
Abstract : Background . Within the past decade, Africa has faced several recurrent outbreaks of Ebola virus disease (EVD), including the 2014-2016 outbreak in West Africa and the recent 2018-2020 Kivu outbreak in the Democratic Republic of Congo. The study thus aimed at quantifying and mapping the scientific output of EVD research published within 2010-2020 though a bibliometric perspective. Methods . EVD-related publications from 2010 to 2020 were retrieved from the Web of Science (WoS) and Scopus databases by using the keywords 'Ebola', 'Ebola Virus Disease', 'Ebolas', and 'ebolavirus'. Biblioshiny software (using R-studio cloud) was used to categorise and evaluate authors', countries' and journals' contribution. VOSviewer was used for network visualisation. Results . According to the used search strategy, a total of 3865 and 3848 EVD documents were published in WoS and Scopus, respectively. The average citation per document was 16.1 (WoS) and 16.3 (Scopus). The results show an overall increase in the publication trend within the study period. The leading countries in EVD research were the USA and UK, with over 100 papers in both databases, including Nigeria and South Africa. NIAID and CDC-USA were the most influential institutions, while "Infectious Diseases" and "Medicine" were the most decisive research fields. The most contributing authors included Feldmann H and Qiu XG with over 60 papers in each database, while Journal of Infectious Diseases was the most crucial journal. The most cited article was from Aylward et al. published in 2014, while recent years displayed a keyword focus on "double-blind", "efficacy", "ring vaccination" and "drug effect". Conclusion . This bibliometric analysis provides an updated historical perspective of progress in EVD research and has highlighted the role played by various stakeholders. However, the contribution of African countries and institutions is not sufficiently reflected, implying a need for increased funding and focus on EVD research for effective prevention and control.